When Are Minorities Worse Off? a Systematic Investigation of Size and Status - Thacker, Strom C.; Lu, Yuan; Gerring, John; Öncel, Erzen (Routledge Journals, Taylor & Francis Ltd, 2017)
Are smaller ethnic groups less advantaged than large groups? This question has not been systematically studied. Using two new datasets, we find that when group size and status are analyzed at national levels smaller groups are generally worse off than larger groups. By contrast, when group size and status are analyzed at subnational (regional or district) levels, smaller groups are better off than larger groups. National minorities are disadvantaged while local minorities are advantaged.We theorize that two factors are at work in generating this surprisingly consistent relationship. First, a synergy exists at national levels among three features of ethnic groups: size, power, and status. The second factor is based on social dynamics. Specifically, insofar as internal migration is characterized by positive selection, then migrants and their descendants should form the basis of small, privileged groups within the region that they migrate to. Insofar as distance enhances positive selection, this explains why smaller migrations are associated with more privileged groups and larger migrations with somewhat less privileged groups.
Erzen Öncel (MEF Author)
Keywords: Minority; Ethnicity; Human development